2017
DOI: 10.1128/mcb.00574-16
|View full text |Cite
|
Sign up to set email alerts
|

HuR Enhances Early Restitution of the Intestinal Epithelium by Increasing Cdc42 Translation

Abstract: The mammalian intestinal mucosa exhibits a spectrum of responses after acute injury and repairs itself rapidly to restore the epithelial integrity. The RNAbinding protein HuR regulates the stability and translation of target mRNAs and is involved in many aspects of gut epithelium homeostasis, but its exact role in the regulation of mucosal repair after injury remains unknown. We show here that HuR is essential for early intestinal epithelial restitution by increasing the expression of cell division control pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 67 publications
7
46
0
Order By: Relevance
“…Polysome analysis was performed as described previously (51). Briefly, cells at ϳ70% confluence were incubated for 15 min in 0.1 mg/ml cycloheximide, lifted by scraping in 1 ml of polysome extraction buffer, and lysed on ice for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Polysome analysis was performed as described previously (51). Briefly, cells at ϳ70% confluence were incubated for 15 min in 0.1 mg/ml cycloheximide, lifted by scraping in 1 ml of polysome extraction buffer, and lysed on ice for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…To examine changes in ␣4 expression in response to the stressful environment in IECs, we employed a previously described (5) in vitro repair model that mimics the early cell division-independent stage of intestinal epithelial restitution. As reported previously (5,23), epithelial restitution occurred rapidly after wounding, as revealed by a significant increase in cell migration over the wounded area by 6 h (data not shown). Interestingly, the levels of ␣4 protein increased remarkably 1 h after wounding and remained elevated for an additional 5 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Paneth cells, which secrete antibacterial peptides and growth factors, however, reside at the base of the crypt area of the intestinal mucosa. The maintenance of apical-basal polarity of intestinal epithelial cells (IECs) depends on a dynamic balance among multiple cellular activities, including proliferation, differentiation, migration, and apoptosis, that are tightly regulated by distinct signaling networks (4,5). Disruption of the integrity of the intestinal epithelium occurs commonly in various critical pathological conditions, leading to the translocation of luminal toxic substances and bacteria to the bloodstream and, in some instances, multiple-organ dysfunction syndromes and death (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cooperative inhibition of IGF2R expression by CUGBP1 and miR-195 was not surprising, as several studies showed that CUGBP1 functionally interacts with miRNAs and/or other RBPs to remodel ribonucleoprotein complexes and influence the posttranscriptional fate of mRNAs positively or negatively (14,37). For example, CUGBP1 interacts with miR-222 to inhibit translation of the Cdk4 mRNA synergistically (18), but it competes with HuR to regulate translation of the tight junction occludin and transcription factor MYC antagonistically (25,26).…”
Section: Discussionmentioning
confidence: 99%